The Effect of Cash Turnover and Current Ratio on Return On Asset at PT Pyridam Farma Tbk Period 2010-2022 - Choiril Anam, Akhmad (Indonesian Financial Review, 2024)
This study aims to determine the effect of Cash Turnover and Current Ratio simultaneously on Return On assets in Pt Pyridam Farma Tbk for the 2010-2022 period. This type of research is associative with a quantitative approach. The methods used are descriptive statistical tests, classical assumption tests, and hypothesis tests. The Cash Turnover study results showed no partial effect on Return On Asset with a calculated value of -0.596< a t-table value of 2.2009, a t-test value of 0.563 > 0.05. The results of the Current Ratio study also have no partial effect on return on assets. This is evidenced by the t-statistic Current Ratio value of 0.687 < ttable value of 2.009 and the significance value of 0.577 > 0.05. From the study results, the effect of Cash Turnover and Current Ratio did not signify on Return On Assets.